Rapid-onset cancer - Andrea Bilger; Paul F. Lambert (Tumour Virus Research)
Human cancers are generally thought to develop over the course of decades. Such slow progression is well documented for a variety of cancers that we designate “slow-onset” cancers. “Rapid-onset” cancers, in contrast, can develop in a matter of months in humans or in as little as 9 days in mice. These cancers often develop under conditions that might be expected to accelerate cancer development: early development, immune deficiency, or viral infection. We will discuss rapid-onset cancers in the context of the ''hallmarks of cancer'' – properties cells must acquire in order to become malignant – focusing on how viruses are particularly well suited to causing rapid-onset cancer.